Dirac line nodes and effect of spin-orbit coupling in the nonsymmorphic critical semimetals MSiS (M=Hf, Zr) - Chen, C.; Xu, X.; Jiang, J.; Wu, S. -C.; Qi, Y. P.; Yang, L. X.; Wang, M. X.; Sun, Yan; Schroeter, N. B. M.; Yang, H. F.; Schoop, L. M.; Lv, Y. Y.; et al. (Physical Review B, 2017)
Topological Dirac semimetals (TDSs) represent a new state of quantum matter recently discovered that offers a platform for realizing many exotic physical phenomena. A TDS is characterized by the linear touching of bulk (conduction and valance) bands at discrete points in the momentum space [i.e., three-dimensional (3D) Dirac points], such as in Na3Bi and Cd3As2. More recently, new types of Dirac semimetals with robust Dirac line nodes (with nontrivial topology or near the critical point between topological phase transitions) have been proposed that extend the bulk linear touching from discrete points to one-dimensional (1D) lines. In this paper, using angle-resolved photoemission spectroscopy (ARPES), we explored the electronic structure of the nonsymmorphic crystals MSiS (M=Hf, Zr). Remarkably, by mapping out the band structure in the full 3D Brillouin zone (BZ), we observed two sets of Dirac line-nodes in parallel with the kz axis and their dispersions. Interestingly, along directions other than the line nodes in the 3D BZ, the bulk degeneracy is lifted by spin-orbit coupling (SOC) in both compounds with larger magnitude in HfSiS. Our paper not only experimentally confirms a new Dirac line-node semimetal family protected by nonsymmorphic symmetry but also helps understanding and further exploring the exotic properties, as well as practical applications of the MSiS family of compounds.
CRIS-Team Scopus Importer:2022-04-14